Spurgeon, Byron, and the Contingencies of Mediation - Mole, Tom (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2010)
The popular Victorian preacher Charles Haddon Spurgeon referred to Byron almost forty times in his published works. Drawing on first-hand examination of Spurgeon’s library, this essay shows how Byron’s words were mediated to Spurgeon through a variety of anthologies, primers, and collections of sententiae, and how Spurgeon mediated them to others in turn through his sermons and writings. In the process, Byron’s writing was broken into fragments, placed in new contexts, spliced with other people’s words, misremembered, misattributed and rendered strange. The essay suggests that analysing this contingent process of mediation reveals alternative possibilities for the study of reception history.